PERANCANGAN SISTEM LAPORAN KEUANGAN SEKOLAH MI ASIA AFRIKA BERBASIS WEBSITE - Lukman Mahdi; Ezra Musa Robo; Alan Nuari; Wasis Haryono (Journal of Research and Publication Innovation, 2025)
This study aims to design a web-based financial reporting system for MI Asia Afrika to improve the efficiency, transparency, and accuracy of financial record-keeping. Using the Waterfall development method, the system was designed through stages including requirement analysis, design, implementation, and testing. The implementation results show that the system supports structured recording of school income and expenditures and facilitates the preparation of real-time financial reports. The system also provides easy access for authorized school personnel.